Genomic and Virulence Characterization of Intrauterine Pathogenic Escherichia coli With Multi-Drug Resistance Isolated From Cow Uteri With Metritis - Ma, Zhengxin; Ginn, Amber; Kang, Minyoung; Galvão, Klibs N.; Jeong, Kwangcheol Casey (Frontiers in Microbiology, 2018)
Metritis is a major disease in dairy cows causing animal death, decrease of birth rate, milk production and economic loss. Antibiotic treatment is generally used to treat such disease but has a high failure rate of 23-35%. The reason for the treatment failure remains unclear, although antibiotic resistance is postulated as one of factors. Our study investigated the prevalence of extended spectrum β-lactamase (ESBL) producing bacteria in uterine samples of cows with metritis and characterized the isolated intrauterine pathogenic E. coli (IUPEC) strains using whole genome sequencing. We found that cows with metritis had a high prevalence of ESBL producing IUPEC with multi-drug resistance including ceftiofur which is commonly used for metiritis treatment. The ESBL producing IUPEC strains harbored versatile antibiotic resistance genes conferring resistance against 29 antibiotic classes, suggesting that transmission of these bacteria to other animals and humans may lead to antibiotic treatment failure. Furthermore, these strains had strong adhesion and invasion activity, along with critical virulence factors, indicating that they may cause infectious disease in not only the uterus, but also in other organs and hosts.